Q5:
If (y+3)(y-1) – (y-2)(y-1) = r(y-1), what
is the value of y?
(1) r2
= 25
(2) r =
5
A. Statement (1) ALONE is sufficient,
but statement (2) alone is not sufficient.
B. Statement (2) ALONE is
sufficient, but statement (1) alone is not sufficient.
C. BOTH statements TOGETHER
are sufficient, but NEITHER statement ALONE is sufficient.
D. EACH statement ALONE is
sufficient.
E. Statements (1) and (2) TOGETHER
are NOT sufficient.
Answer:
感觉应该是r不等于5时,才能推出y=1
如果r=5,y任何值都满足情况啊。
因为y不等于1时,有(y+3)-(y-2)=y+3-y+2=5=r
欢迎光临 ChaseDream (https://forum.chasedream.com/) | Powered by Discuz! X3.3 |